Why We Meditate : The Science and Practice of Clarity and Compassion - Goleman, Daniel; Tsoknyi Rinpoche (New York : Atria Books, 2022)
"WHY WE MEDITATE by Daniel Goleman, the New York Times-bestselling author of Emotional Intelligence and many other books, and Tsoknyi Rinpoche, an internationally recognized and beloved spiritual guide in the Tibetan Buddhist community, presents scientifically backed and time-proven Eastern meditation practices that offer an antidote to the forces of frenzy and stress that awash us"--
What this book offers you -- Drop it! -- Belly breathing -- Beautiful monsters -- Essence love -- Love and compassion -- Calm and clear -- A deeper look within -- Epilogue: Some final advice.
Includes bibliographical references and index.
Keywords: Meditation; Mind and body; Mindfulness (Psychology)